PROMBot-HSM-AF: protocol for a feasibility study of a chatbot-based platform to collect patient-reported outcomes after atrial fibrillation ablation - Sérgio Laranjo; Pedro Silva Cunha; Federico Guede-Fernández; Eduarda Oliosi; Rita Contins; Pedro Dias; Catarina Silva; Ana Clara Félix; Mário Martins Oliveira; Ana Rita Londral (Frontiers in Cardiovascular Medicine, 2026)
Introduction Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, with catheter ablation increasingly recommended as first-line therapy. Despite its effectiveness, 15% to 20% of patients require reassessment within the first month post-procedure. Standard follow-up relies on scheduled consultations and intermittent monitoring, which may delay recognition of recurrence or complications. Remote patient monitoring through conversational agents may address these gaps, yet evidence on feasibility and implementation in post-ablation care remains limited. This study aims primarily to evaluate the feasibility, usability, and acceptability of PROMBot-HSM-AF (Chatbot Platform to Collect Patient-reported Outcomes After AF Ablation, Santa Marta Hospital) during the first 3 months following AF catheter ablation. Methods and analysis PROMBot-HSM-AF is a single-center, open-label, randomized controlled pilot (feasibility) trial with two parallel groups, conducted at Santa Marta Hospital, Lisbon, Portugal. Seventy-six patients undergoing AF ablation will be randomized in a 1:1 ratio to either chatbot-supported follow-up or standard care. The primary feasibility parameters are: recruitment rate (proportion of eligible patients consenting), retention rate at 3 months, and chatbot engagement rate (proportion of chatbot prompts answered). Acceptability and usability will be assessed using behavioral indicators (engagement and retention), the System Usability Scale (SUS), the Post-Study System Usability Questionnaire (PSSUQ), and semi-structured interviews with patients and healthcare professionals. Quantitative data will be analyzed descriptively with exploratory between-group comparisons. Semi-structured interviews with patients and healthcare professionals will be analyzed using thematic content analysis. Conclusions This pilot trial will provide preliminary evidence on the feasibility and acceptability of integrating a chatbot-based platform into routine post-ablation care. Findings will inform refinement of the intervention and future effectiveness research in this population. The study addresses a critical gap in remote patient monitoring for post-procedural care. Clinical Trial Registration https://clinicaltrials.gov/study/NCT07237178 , identifier NCT07237178.